Live/Real Time Three-Dimensional Transesophageal Echocardiographic Evaluation of Mitral and Aortic Valve Prosthetic Paravalvular Regurgitation - Singh, Preeti; Manda, Jayaprakash; Hsiung, Ming Chon; Mehta, Anjlee; Kesanolla, Saritha Kumari; Nanda, Navin C; Tsai, Shen-Kou; Wei, Jeng; Yin, Wei-Hsian (Cardiovascular Journal, 2010)
Thirteen patients already scheduled for surgery for repair of prosthetic paravalvular regurgitation underwent intraoperative real time two-dimensional transesophageal echocardiography (2D TEE) and live/real time three-dimensional transesophageal echocardiography (3D TEE). In all patients, 3D TEE was able to provide more information regarding the location and size of the paravalvular defect as compared to 2D TEE. 3D TEE resulted in a more accurate localization of the defect and an estimation of the size of the defect that correlated much more closely with surgical findings when compared with 2D TEE. Our preliminary results demonstrate the superiority of 3D TEE over 2D TEE in the evaluation of paravalvular prosthetic regurgitation. 3D TEE not only provides an accurate assessment of the exact site of the leakage, but also gives a more accurate estimate of its size. This information could be valuable to surgeons who may encounter difficulty when localizing and estimating the size of paraprosthetic leaks while the heart is devoid of blood during surgery. Keywords: Three-dimensional echocardiography; Three-dimensional transesophageal echocardiography; Prosthetic paravalvular regurgitation; prosthetic valves; Transesophageal echocardiography DOI: 10.3329/cardio.v2i2.6627 Cardiovasc. j. 2010; 2(2) : 121-127